Transfer teknologi pakan organik 'maggot' sebagai upaya peningkatan produktivitas ikan air tawar masyarakat Gampong Dham Pulo, Aceh Besar (Transfer of organic feed technology maggot as an effort to increase freshwater fish productivity, Dham Pulo Village, Ingin Jaya Sub-District, Aceh Besar) - Putra, Dedi Fazriansyah; Almerian, Ivan; Al-Qossam, Izzuddin; Munthe, Aris Darmika; Barizki, Gebrina Zikra; Isvalana, Nabila; Mirnawati, Windy; Aidil, Jul; Zuhra, Annisa; Rahayu, Silvana; Harahap, Putri Dyana; Farisi, Wilma; Gheitsa, Tjut Nyak Ghalda; Aiza, Nur; Alfani, Fatha Yufari; Harahap, Riqqa Rahmania Sallim; Jalil, Zulkarnain; Feriyanto, Reki (Buletin Pengabdian, 2022)
The objectives of this community service implementation are; provide information to the public how to make fish feed that is cheap, easy, and environmentally friendly so that people do not have trouble getting fish feed raw materials. Community Service in the Holistic Village Development and Guidance Program (PHP2D) was carried out in Dham Pulo Village (Gampong), Want Jaya District, Aceh Besar District, from August to December 2021. The general stages of this activity consist of 4 (four) stages main activities, namely: socialization and training on maggot organic feed technology, independent bioconversion-based organic feed manufacturing practices, training on digitalization of marketing fishery products, websites and social media and evaluation in the form of workshops or FGDs involving all stakeholders such as the village government, fisheries service and private agencies. . The results obtained from this activity are the information obtained regarding the technology of maggot cultivation independently as a substitute for catfish feed. The conclusion of this PHP2D activity is that the community can increase their skills in maggot cultivation techniques (Hermetia Illucens) independently which can be used as an alternative to pellets as fish feed.